2018
DOI: 10.1080/17411548.2018.1442620
|View full text |Cite
|
Sign up to set email alerts
|

Greek cinema as European cinema: co-productions, Eurimages and the Europeanisation of Greek cinema

Abstract: Around the start of the 2010s, while Greece found itself in the midst of a deep financial, political and social crisis that troubled its relationship to Europe, Greek cinema was being noticed in prestigious film festivals. Soon the term 'Weird Wave' was adopted to suggest the unusual aesthetics and challenging ethics of the most distinctive films that emerged from this troubled nation at the time: Yorgos Lanthimos' Dogtooth (2009) and Athina Rachel Tsangari's Attenberg (2010). Despite being made before the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The restoration and development of cinema began to gain momentum and rapidly release new products because of social and political events that took place in Ukraine in . Papadimitriou (2018, wrote that an outstanding event and a new stage for Ukrainian cinema was creation of the "Babylon-13" studio.…”
Section: Renaissance Of Ukrainian Cinemamentioning
confidence: 99%
See 3 more Smart Citations
“…The restoration and development of cinema began to gain momentum and rapidly release new products because of social and political events that took place in Ukraine in . Papadimitriou (2018, wrote that an outstanding event and a new stage for Ukrainian cinema was creation of the "Babylon-13" studio.…”
Section: Renaissance Of Ukrainian Cinemamentioning
confidence: 99%
“…All young filmmakers aspiring to create new films and restore the Ukrainian film industry gathered under Tykhy's leadership. Papadimitriou (2018), indicated that the "Babylon-13" studio has released a number of iconic Ukrainian films, including "Euromaidan. Rough Cut" by Volodymyr Tykhy, "Maidan" by Serhiy Loznytsia, "Winter on Fire" and "Heavenly Hundred" by Yulia Gontaruk and Roman Lyuby.…”
Section: Renaissance Of Ukrainian Cinemamentioning
confidence: 99%
See 2 more Smart Citations